Air-Drying: A Simple Method for the Preservation of Hollow Organs and Lungs to Contribute to the Teaching of Anatomy - Abumandour, Mohamed Mohamed Abd El-Rahman; El-Bakery, Raafat Mohamed Ahmed (Journal of Morphological Sciences, 2019)
The present study describes air-drying, which is an alternative method to study and teach gross anatomy to undergraduate and postgraduate students. In order to preserve the hollow organs of different animals, an air-drying pump (compressor) was used; then, the preserved specimens were expanded through the injection of foam into their lumen followed by the application of varnish on their external surface to protect them from insect damage. This method of preservation is suitable for developing countries because it is cheap to prepare, simple to perform, and can be performed at room temperature (37°-40°C) without special equipment. The produced specimens have many advantages: their normal anatomical form remains durable, very light in weight, non- toxic regarding handling, and resistant to improper handling and deterioration by fungi or bacteria, with all structures very clear. These preserved specimens last for many years without any changes.
Keywords: anatomy; preservation; air -drying; hollow organs; Lungs